(1,1-Diphenyl-2-Picrylhydrazyl) free radical scavenging activity of white tea base on temperature and period of brewing - Dadan Rohdiana; Dede Zainal Arief; Mamay Somantri (Research Institute for Tea and Cinchona, 2013)
Research of 1,1-Diphenyl-2-Picrylhydrazyl (DPPH) free radical scavenging activity has been done conducted on Laboratory of Quality Assesment, Research Institute for Tea and Cinchona, and Laboratory of Chemistry, Chemistry Department, Faculty of Matematic and Natural Science, Padjdjaran University. The result showed that among four white tea from different estates, total polyphenol content on Gambung White Tea has the highest. Total polyphenol content of Gambung white tea i.e 25,52%. Brewing process on 95oC for 9 minutes obtained the highest polyphenol content on tea infusion i.e. 6,01% and the lowest EC50 i.e. 35,41 Âµl/ml. This research showed that presence of positive correlation between total polyphenol and antioxidant activity base on EC50. The correlation value in this research i.e. 0,9066.